1978
DOI: 10.1128/iai.19.3.893-897.1978
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resistance Against Junin Virus Infection Induced by Corynebacterium parvum

Abstract: The effects of intraperitoneal administration of Corynebacterium parvum on the course of Junin virus infection in mice were investigated. This treatment produced enhanced resistance to the virus infection, evidenced by an increase in both survival times and the proportion of survivors. The protective effect was dependent upon the dose of C. parvum , and 280 μg/g of body weight was found to be the optimal dose. In various experiments, about 80% of the infected ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…However, it should be noted that P. acnes can also activate suppressor macrophages (10) which, in turn, may limit immunopathological damage resulting from infiltrating cytotoxic cells. Suppression of cytotoxic T-cell activity has been proposed as a mechanism for the P. acnes-induced enhancement of murine resistance to the hemorrhagic arenavirus Junin (9); however, the kinetics of the P. acnes-induced protective effects observed in our studies differ from those observed in the Junin studies.…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…However, it should be noted that P. acnes can also activate suppressor macrophages (10) which, in turn, may limit immunopathological damage resulting from infiltrating cytotoxic cells. Suppression of cytotoxic T-cell activity has been proposed as a mechanism for the P. acnes-induced enhancement of murine resistance to the hemorrhagic arenavirus Junin (9); however, the kinetics of the P. acnes-induced protective effects observed in our studies differ from those observed in the Junin studies.…”
Section: Resultscontrasting
confidence: 81%
“…Certain strains of propionibacteria which were formerly classified as Corynebacterium parvum have the ability to cause intense stimulation of the mononuclear phagocyte system, as manifested by enlargement of the spleen and liver and enhanced clearance of particles from the bloodstream (2, 10,24,37). Depending on the time and route of inoculation, these strains can enhance antibody production (2,10,26,37) and resistance to viral (9,11,23,28,30,35,36), bacterial (1,15,45), and protozoan (8,14) infections. The macrophage appears to be a critical element for many of the stimulatory activities induced by the propionibacteria (2), and it is believed that macrophage activation is primarily responsible for augmentation of resistance.…”
mentioning
confidence: 99%
“…Moreover, Budzko et al 32 showed a dose‐dependent response in Junin virus infection in mice: 280 mcg injected intraperitoneally uplifted the survival rate to 80% compared with 20% of the untreated animals. Naficy et al 33 reported the antiviral activity of five different C.parvum strains in comparison with simple vaccination, stressing an effective adjuvant role.…”
Section: Introductionmentioning
confidence: 99%